One-dimensional potassium sodium niobates (1D KNN): Performance optimization and application prospects - Lei Jiang; Tingting Shao; Xinran Yang; Juan Xiong; Yongming Hu; Zhao Wang; Haoshuang Gu; John Wang (Journal of Materiomics)
One-dimensional (1D) nanostructures of perovskite piezoelectrics exhibit unique properties that distinct them from those of their bulk and thin-film counterparts. These 1D nanostructures feature cantilever-like flexibility and elasticity, a relatively high piezoelectric constant, good stability and easiness of integration, making them highly promising for applications in energy harvesting, pressure sensing, piezo-catalysis, nano-actuators and smart human-machine interfaces. Among them, (K,Na)NbO3 (KNN) has been regarded as one of the most promising lead-free perovskite piezoelectrics owing to its excellent biocompatibility, good piezoelectric performance, and high Curie temperature. Recently, significant efforts have been made to develop high-performance 1D KNN nanostructures (1D KNNs). However, the controllable growth and enhancement in piezoelectric performance of 1D KNNs remain challenging. In this work, we systematically re-examine the effective approaches for the growth of 1D KNNs and explore their unique properties. Key strategies for structural designs and performance optimization are proposed based on the recent progress, along with perspectives in developing novel functionalities and micro/nano-devices such as energy harvesters, information storage, electronic skins, biomedical applications.